2020
DOI: 10.1101/2020.06.16.20133025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of antibodies to the SARS-CoV-2 spike glycoprotein in both serum and saliva enhances detection of infection

Abstract: Background: Detecting antibody responses during and after SARS-CoV-2 infection is essential in determining the seroepidemiology of the virus and the potential role of antibody in disease. Scalable, sensitive and specific serological assays are essential to this process. The detection of antibody in hospitalized patients with severe disease has proven straightforward; detecting responses in subjects with mild disease and asymptomatic infections has proven less reliable. We hypothesized that the suboptimal sensi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 24 publications
6
73
0
2
Order By: Relevance
“…A2 and C3 had a low level but detectable neutralizing antibody activity in sera on days 12 and 37, respectively. Serological responses to SARS-CoV-2 are associated with disease severity 20,21 , although data from children who often have milder disease or are likely to be asymptomatic are limited. In our study, children had low to undetectable serum antibodies while both parents had strong serum IgG responses out to day 88.…”
Section: Resultsmentioning
confidence: 99%
“…A2 and C3 had a low level but detectable neutralizing antibody activity in sera on days 12 and 37, respectively. Serological responses to SARS-CoV-2 are associated with disease severity 20,21 , although data from children who often have milder disease or are likely to be asymptomatic are limited. In our study, children had low to undetectable serum antibodies while both parents had strong serum IgG responses out to day 88.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation for the presence of antibodies in saliva of large cohorts of individuals could better determine the prevalence of COVID-19, monitor disease progression, and help define previous exposure to SARS-CoV-2 in populations (Béné et al 2020). In fact, 2 non-peer-reviewed articles were recently published online demonstrating that the temporal kinetics of IgG, IgA, and IgM in the saliva of patients with COVID-19 were consistent with those observed in serum (Randad et al 2020) and that antibodies (IgA, IgG, and IgM) to the SARS-CoV-2 spike glycoprotein could be detected in serum and saliva (Faustini et al 2020).…”
Section: Salivary Biomarkers For Covid-19: New Research Directionsmentioning
confidence: 97%
“…Active infection can be detected by molecular-based testing for viral RNA, but this approach cannot be used for seroprevalence investigations. Antibody testing on blood samples (or saliva) is useful for determining historic exposure to the virus and may provide insight into the immunological status of the individual ( Faustini et al 2020 ). It can be performed both by lateral flow assay (LFA) directly in the field or by enzyme-linked immunosorbent assay (ELISA) and/or chemiluminiscent assay technologies in a centralized laboratory.…”
Section: Antibody Testing In the Salivamentioning
confidence: 99%
“…In one of these studies, antispike (but not nucleocapsid) IgG, IgA, and IgM antibody responses were readily detectable in saliva from nonhospitalized symptomatic and asymptomatic patients. Interestingly, antibody responses in the saliva and serum and symptoms are largely independent of one another ( Faustini et al 2020 ). In contrast to these results, another study evaluated the results of a multiplex immunoassay to detect specific antibodies in the crevicular fluid and found that SARS-CoV-2 antigen-specific IgG responses in matched serum and saliva samples were significantly correlated.…”
Section: Antibody Testing In the Salivamentioning
confidence: 99%